D-index and invasive fungal infections (IFIs) in adult acute myeloid leukemia (AML) patients with the first episode of febrile neutropenia. - Thanawat Rattanathammethee; Kawin Munsamai; Teerachat Punnachet; Nonthakorn Hantrakun; Pokpong Piriyakhuntorn; Sasinee Hantrakool; Chatree Chai-Adisaksopha; Ekarat Rattarittamrong; Adisak Tantiworawit; Lalita Norasetthada (PLoS ONE, 2023)
Introduction This study aimed to evaluate the performance of the D-index, a calculated measure of neutropenic burden, in predicting the risk of invasive fungal infections (IFIs) in acute myeloid leukemia (AML) patients. Methods A retrospective study of adult AML patients who received the first induction chemotherapy and developed febrile neutropenia was conducted. Clinical characteristics, laboratory data, and the calculation of the D-index and cumulative D-index (c-D-index) were collected and analyzed between patients with and without IFIs. Results A total of 101 patients were included, with 16 (15.8%) patients who developed IFIs. Clinical characteristics, antifungal prophylaxis, and AML cytogenetic risk were similar between patients with or without IFIs. The results showed that the D-index and c-D-index were more effective in predicting IFIs than the duration of neutropenia. With the D-index cutoff of 7083, the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 81.3%, 83.5%, 48.2%, and 95.9%, respectively. c-D-index at 5625 revealed sensitivity, specificity, PPV, and NPV for IFIs of 68.8%, 68.2%, 28.9%, and 92.1%, respectively. Using this cutoff of c-D-index, patients without IFIs were overtreated with an antifungal regimen in 45 (52.9%) cases. Conclusion The D-index and c-D-index were helpful indicators for defining the risk of IFIs in AML patients with febrile neutropenia.